The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/2472555217731556
|View full text |Cite
|
Sign up to set email alerts
|

Erastin-Like Anti-Warburg Agents Prevent Mitochondrial Depolarization Induced by Free Tubulin and Decrease Lactate Formation in Cancer Cells

Abstract: In Warburg metabolism, suppression of mitochondrial metabolism contributes to a low cytosolic ATP/ADP ratio favoring enhanced aerobic glycolysis. Flux of metabolites across the mitochondrial outer membrane occurs through voltage-dependent anion channels (VDAC). In cancer cells, free dimeric tubulin induces VDAC closure and dynamically regulates mitochondrial membrane potential (ΔΨ). Erastin, a small molecule that binds to VDAC, antagonizes the inhibitory effect of tubulin on VDAC and hyperpolarizes mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 36 publications
1
41
1
Order By: Relevance
“…In a previous high content small molecule screening, X1 and X4 (Fig. 2) were identified as the two most potent structurally unrelated lead compounds that antagonized mitochondrial depolarization caused by high cellular free tubulin in HCC4006 lung carcinoma cells [26]. In HepG2 cells loaded with TMRM, both 10 µM X1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous high content small molecule screening, X1 and X4 (Fig. 2) were identified as the two most potent structurally unrelated lead compounds that antagonized mitochondrial depolarization caused by high cellular free tubulin in HCC4006 lung carcinoma cells [26]. In HepG2 cells loaded with TMRM, both 10 µM X1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we showed that erastin antagonizes the inhibitory effects of tubulin on VDAC. After identifying erastin as the first known pharmacological antagonist of the inhibitory effect of free tubulin on VDAC, we identified by high content cell-based screening several erastin-like small molecules that also appear to prevent VDAC closure by high free cytosolic tubulin [26]. Here, we assess the hypothesis that increased mitochondrial metabolism after VDAC opening leads to enhanced mitochondrial generation of reactive oxygen species (ROS), mitochondrial dysfunction, bioenergetic failure and cell death.…”
Section: Introductionmentioning
confidence: 99%
“…The six lead compounds hyperpolarized mitochondria without causing changes in tubulin polymerization in a dose-dependent fashion. Erastin and the most potent X1 not only increased mitochondrial metabolism but had an anti-Warburg effect evidenced by the decreased lactate release in HepG2 and Huh7 hepatocarcinoma cells and HCC4006 lung carcinoma cell lines (DeHart, Lemasters, & Maldonado, 2017). …”
Section: Vdac–tubulin Antagonists: a Strategy For Opening Vdacmentioning
confidence: 99%
“…The erastin-like anti-Warburg compound X1 also decreases glycolysis as evidenced by a decrease in lactate release (DeHart et al, 2017). The combination of reversal of Warburg metabolism and oxidative stress by the lead compound caused cell death to human hepatocarcinoma cell lines in culture and to xenografted Huh7 hepatocarcinoma cells (Fig.…”
Section: Vdac–tubulin Antagonists: a Strategy For Opening Vdacmentioning
confidence: 99%
“…It has been recently proposed that VDAC operates as a switch for global control of mitochondrial metabolism in cancer cells. Moreover, small molecules that cause VDAC opening increase mitochondrial metabolism and generation of ROS and decrease levels of enhanced glycolysis, acting as anti-Warburg compounds ( Maldonado, 2017 )( DeHart, 2017 )( Fang, 2018 )( Heslop, 2020 )(Maldonado, 2017; DeHart et al, 2018; Maldonado and Fang, 2018; Heslop et al, 2020).…”
Section: Introductionmentioning
confidence: 99%